2020
DOI: 10.1038/s41598-020-69905-z
|View full text |Cite
|
Sign up to set email alerts
|

A lncRNA landscape in breast cancer reveals a potential role for AC009283.1 in proliferation and apoptosis in HER2-enriched subtype

Abstract: Breast cancer is the most commonly diagnosed neoplasm in women worldwide with a well-recognized heterogeneous pathology, classified into four molecular subtypes: Luminal A, Luminal B, HER2enriched and Basal-like, each one with different biological and clinical characteristics. Long noncoding RNAs (lncRNAs) represent 33% of the human transcriptome and play critical roles in breast carcinogenesis, but most of their functions are still unknown. Therefore, cancer research could benefit from continued exploration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Recent bioinformatic research has identified an immune-related lncRNA signature model to predict the risk of 5-year recurrence-free survival in BC (Lai et al, 2020). Other studies have depicted the lncRNA landscape using transcriptome microarrays in BC and identified deregulated lncRNA expression patterns across different molecular subtypes (Cedro-Tanda et al, 2020). However, the overall perspective of m6A regulators involved in the dysregulation of lncRNAs in BC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent bioinformatic research has identified an immune-related lncRNA signature model to predict the risk of 5-year recurrence-free survival in BC (Lai et al, 2020). Other studies have depicted the lncRNA landscape using transcriptome microarrays in BC and identified deregulated lncRNA expression patterns across different molecular subtypes (Cedro-Tanda et al, 2020). However, the overall perspective of m6A regulators involved in the dysregulation of lncRNAs in BC is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation analysis between the DE-lncRNAs and DE-m6A regulators identified 2,479 m6A-related lncRNAs (Spearman's correlation >0.3 or < −0.3). As the lncRNAs were associated with cancer subtypes (Cedro-Tanda et al, 2020;Arnes et al, 2019), the m6A-related lncRNAs could also clearly stratify the COAD samples into three subtypes. We found that nearly 40% of samples in the subtype 2 had microsatellite instability (MSI), which was significantly higher than in the two other subtypes.…”
Section: Discussionmentioning
confidence: 97%
“…Using the BRCA cohort previously reported by our group in ( 62 ) (n = 74; Luminal A = 24, Luminal B = 23, HER2 = 14, Basal = 13) in which samples were analyzed using Human Transcriptome Array 2.0 (Affymetrix, Inc, Santa Clara, CA), we were able to identify LINC00460 expression levels across BRCA subtypes. We used the Robust Multi-chip Analysis (RMA) algorithm to minimize the effect of probe-specific affinity differences and to normalize samples ( 63 ).…”
Section: Methodsmentioning
confidence: 99%